'We are the new Jews!' and 'The Jewish Lobby' – antisemitism and the construction of a national identity by the Austrian Freedom Party. Issue 3 (1st March 2016) - Stoegner, Karin
Abstract: In this article I will analyse the role of antisemitism for the construction of a national identity and an exclusive national in‐group in the discourse of the Austrian Freedom Party (FPÖ). The analysis will show that this discourse of the FPÖ, one of the most successful extreme right‐wing parties in Europe, utilises various forms of Holocaust inversion and victim perpetrator reversal in order to delegitimise political opponents. The analysis of these incidents and of the legitimising strategies used by the FPÖ when criticised involves discussing the increasing abstraction of the codes characteristic of latent antisemitism and forms of post‐Nazi antisemitism. I will focus on how the FPÖ's use of the term Holocaust and other terms referring to Nazi atrocities against the Jews corresponds to a universalisation of the term Holocaust in social constellations that are permeated by the culture industry.